Measuring Goal Realization Associated With Disability Services and Supports: Initial Evidence for a New Tool. Issue 1 (21st April 2019) - Hagiliassis, Nick; Koritsas, Stella; Cuzzillo, Celeste
Abstract: There are few outcome measurement tools that can be accessed directly by people with intellectual disability (ID) and that can be readily used in service delivery settings. Developed to address these limitations, the Measuring Outcomes in Services and Supports – Short Form is a measure of the extent to which a person's goals are realized in the context of service and supports delivery. Specific aim is to establish initial evidence for the face and content validity of the tool, an essential step in the first stage of developing evaluation tools. Face validity was explored via an on‐line survey eliciting information from an "expert group" about the purpose, adequacy, clarity, and attractiveness of the tool. Content validity was examined by comparing goals for people with disability against a framework for categorizing personal outcomes and their influencers, to gauge the tool's relevance, and representation for measuring whole of life disability outcomes. Participants gave positive support overall for aspects of face validity surveyed. Suggestions for further improvements were provided, most of which were accommodated. Other issues raised reflected themes general to the field of outcomes measurement in disability populations (e.g., complexity for people with ID), with strategies suggested for attenuating their impact. Participant goals were representative of outcome domains reflecting the current policy environment in disability, as were their influencing factors. With limited tools to measure goal realization for people accessing a range of disability supports, the tool has acceptable face validity and content validity and is sufficiently practical for use in disability services.